Analisis Pergeseran Secara Vertikal dan Arah Gerakan Partikel di Jembatan Bantar III Kulon Yogyakarta Akibat Dilewati Kendaraan Menggunakan Metode Mikrotremor - Meilan Demulawa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine how much the maximum vertical displacement of vibrations experienced by the bridge when something passes over it and compare it with the complete removal permitted by SNI 03 – 2847 – 2002. To find out the direction of movement of vibration particles when a vehicle/something crosses the bridge. The maximum vertical displacement value of bridge vibration due to vehicle load experimentally ranges from 8.5 mm – 29.2 mm and theoretically from 127.5 mm – 170 mm. This value (experimentally) is smaller than the results obtained in theory, which means that the bridge structure can still withstand the instantaneous external loads that cross the bridge. At the same time, the direction of movement of the bridge particles passed by vehicles is generally vertical to the direction of the bridge.